Pemberdayaan Masyarakat Korban Tsunami Selat Sunda Kampung Nelayan Teluk Labuan Banten - Sutarman Sutarman; Yuyun Yuniarsih; Maria Grace Herlina (IAI Darussalam, 2019)
contributions in the form of funds; 2) All volunteers must provide motivation to victims; 3) All volunteers must provide therapeutic healing; 4) All volunteers provide good and accurate information. With the implementation of this empowerment, the tsunami victims were greatly helped by the participation of volunteers in helping tsunami victims in the fishing village of Labuan Bay, Banten.